Recent Developments and the New Direction in Soft-Computing Foundations and Applications Selected Papers from the 6th World Conference on Soft Computing, May 22-25, 2016, Berkeley, USA - Zadeh, Lotfi A.; Yager, Ronald R.; Shahbazova, Shahnaz N.; Reformat, Marek Z.; Kreinovich, Vladik; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is an authoritative collection of contributions in the field of soft-computing. Based on selected works presented at the 6th World Conference on Soft Computing, held on May 22-25, 2016, in Berkeley, USA, it describes new theoretical advances, as well as cutting-edge methods and applications. Theories cover a wealth of topics, such as fuzzy logic, cognitive modeling, Bayesian and probabilistic methods, multi-criteria decision making, utility theory, approximate reasoning, human-centric computing and many others. Applications concerns a number of fields, such as internet and semantic web, social networks and trust, control and robotics, computer vision, medicine and bioinformatics, as well as finance, security and e-Commerce, among others. Dedicated to the 50th Anniversary of Fuzzy Logic and to the 95th Birthday Anniversary of Lotfi A. Zadeh, the book not only offers a timely view on the field, yet it also discusses thought-provoking developments and challenges, thus fosteringnew research directions in the diverse areas of soft computing.
Big Data Analytics and Fuzzy Technology: Extracting Information from Social Data -- Personalization and Optimization of Information Retrieval: Adaptive Semantic Layer Approach -- Frequent Itemset Mining for a Combination of Certain and Uncertain Databases -- A New Method for Filling Missing Value Based on the Rough Set Theory -- A Hierarchy-Aware Approach to the Multiaspect Text Categorization Problem -- Adaptive Neuro-Fuzzy Inference System for Classification of Texts -- Game Approach to Fuzzy Measurement -- Towards real-time Lukasiewicz Fuzzy Systems -- Rankings and Total Orderings on Sets of Generalized Fuzzy Numbers -- Bio-inspired optimization metaheuristic algorithm based on the self-defense of the plants -- Experimenting with a New Population-Based Optimization Technique: FUNgal Growth Inspired (FUNGI) Optimizer -- A Hybrid Genetic Algorithm for Minimum Weight Dominating Set Problem -- How to Estimate Resilient Modulus for Unbound Aggregate Materials: A Theoretical Explanation of an Empirical Formula -- Development of NARX based neural network models for predicting air quality near busy urban corridors -- Sustainability Index: A fuzzy Approach for a municipal decision support system. .
Keywords: Computational intelligence; Artificial intelligence; Game theory; Industrial Management; Control engineering; Robotics; Automation; Computational Intelligence; Artificial Intelligence; Game Theory; Industrial Management; Control, Robotics, Automation